Evgeny Vodolazkin’s „The Aviator” as a Diary Genre - Wojciechowska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The purpose of this article is to investigate the diary genre as used in Evgeny Vodolazkin’s novel The Aviator. The author of the paper attempts to describe and emphasize the innovativeness of Vodolazkin’s approach, as compared with the main classic features interpreted in the light of Elena Bogdanova’s article entitled ‘Language features of the diary genre’ (2008) which brings a classification thereof.